Hidden. Series 1 [videorecording (DVD)] - Reese-Williams, Sian, 1981-; Meilir, Rhodri, 1978-; Keyworth, Gwyneth, 1990-; Elisa, Gillian, 1953-; Davies, Sion Alun; Arwyn, Owen; Saynor, Ian; Roberts, Nia, 1972-; Jones, Mark Lewis (Acorn, 2018)
In this noir thriller from the team behind Hinterland, DI Cadi John investigates a string of disappearances in the mountains of Wales.